Bagaimana Kompensasi Membentuk Retensi, Kinerja, dan Niat Berhenti Kerja di Kalangan Generasi Z - Vikar, Kharissa; Wahyuni, Salamah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines how compensation affects employee retention, turnover intention, and job performance, with job satisfaction as a mediating variable among Generation Z employees at PT Shopee International Surakarta. Using a cross-sectional survey, data from 270 respondents were analyzed with PLS-SEM. The results show that compensation increases retention, job performance, and job satisfaction, while reducing turnover intention. Job satisfaction strengthens retention and lowers turnover intention, but does not significantly affect job performance. These findings imply that compensation is essential for retaining Generation Z employees, whereas performance is shaped more by operational systems than satisfaction.